The Characteristics of the Intergeneral Variability of Exterior Indicators in Karakalpak Sur Karakul Sheep - Abdirazakovich, Urimbetov Akhmet (American Journal of Bioscience and Clinical Integrity, 2025)
The article discusses the results of scientific research aimed at studying changes in the exterior characteristics of lambs of the Sur breed depending on the selection of parents belonging to different ethological types. The observations made make it possible to identify features of the dynamics of animal development, as well as to assess the influence of genetic factors on their exterior characteristics. The data obtained are of practical importance for breeding work, making it possible to optimize methods for selecting sires in order to increase productivity and improve the exterior qualities of the offspring.